Control of Leaf Spot Disease of Wrighitia tinctoria Br. in the Forest Nursery - Siddaramaiah, A. L.; Kulkarni, Srikant; Basavarajaiah, A. B. (Indian Forester, 1980)
Eight fungicides were tested in the forest nursery against Cercospora wrighitia Thirum. And Chupp. Which is a destructive pathogen of forest nursery seedlings of Wrighitia tinctoria Br. These fungicides were sprayed thrice at an internl of 20 days. Bavistin was the most effective at a concentration of 0.05 per cent (500 mg/lit of water). Bayletan 0.05 per cent, Duter 0.2 per cent, Brestan 0.2 per cent, Baycor 0.05 per cent and Fytolan 0.2 per cent were also found effective to some extent, Thiram 0.2 per cent and Vitavax 0.1 per cent were not effective.